Pattern recognition receptors and the inflammasome in kidney disease - Leemans, Jaklien C.; Kors, Lotte; Anders, Hans-Joachim; Florquin, Sandrine (Nature reviews. Nephrology, 2014)
Key Points Toll-like receptors (TLRs), nucleotide-binding oligomerization domain receptors (NLRs) and the NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome regulate inflammatory and repair processes in the kidneys TLRs prevent invasion and growth of pathogens in the urinary tract Inappropriate activation of TLRs, NLRs and the NLRP3 inflammasome is a major cause of acute and chronic kidney disease Gene-association studies have revealed connections between TLR gene mutations and the development of several inflammatory kidney disorders TLRs, NLRs and the NLRP3 inflammasome represent attractive novel drug targets to prevent and intervene in kidney inflammation and suppress immunopathology in kidney disease In this Review, the authors discuss the pathological mechanisms related to Toll-like receptors, nucleotide-binding oligomerization domain receptors and the NACHT, LRR and PYD domains-containing protein 3 inflammasome in various kidney diseases. Although these receptors are protective in the host defence against urinary tract infection, they can perpetuate tissue damage in sterile inflammatory and immune-mediated kidney diseases—making them promising drug targets. Toll-like receptors (TLRs) and nucleotide-binding oligomerization domain receptors (NLRs) are families of pattern recognition receptors that, together with inflammasomes, sense and respond to highly conserved pathogen motifs and endogenous molecules released upon cell damage or stress. Evidence suggests that TLRs, NLRs and the NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome have important roles in kidney diseases through regulation of inflammatory and tissue-repair responses to infection and injury. In this Review, we discuss the pathological mechanisms that are related to TLRs, NLRs and NLRP3 in various kidney diseases. In general, these receptors are protective in the host defence against urinary tract infection, but can sustain and self-perpetuate tissue damage in sterile inflammatory and immune-mediated kidney diseases. TLRs, NLRs and NLRP3, therefore, have become promising drug targets to enable specific modulation of kidney inflammation and suppression of immunopathology in kidney disease.